CTD data from LOWPHOX-II cruise off northern Chile, February 2018 - Vargas, Cristian A; Schneider, Wolfgang (PANGAEA, 2025)
Hydrographic measurements from a transect off northern Chile (20° S) are reported. The data were collected using a CTD SBE 9-11 mounted on a rosette. The CTD was equipped with two temperature, conductivity and oxygen sensors, a fluorometer and PAR sensors. The cruise was carried out on the R/V Cabo de Hornos between 3rd and 6th of february 2018.
Keywords: Chile; CTD casts; Fluorescence; Oxygen; PAR